THE INFLUENCE OF THE LEADERSHIP STYLE OF THE VILLAGE HEADMAN AND THE VILLAGE APPARATUS COMPETENCE ON THE SUCCESS OF DEVELOPMENT IN SRIAMUR VILLAGE, BEKASI - Siahaan, Matdio; Komariah, Neng Siti (International Journal of Multidisciplinary Research and Literature, 2022)
As a leader in the village scope, the Village Headman has a leadership style that can influence community participation and motivation to realize good development at all levels of society. The leadership style of the village head is closely related to the goals to be achieved by a village government. Together with the Village Apparatus at the village level, it is hoped that they will be able to carry out the wheels of village government well in providing services to the community so that if the village head shows good performance in administering village government, it will also affect the performance of government at the district, provincial, and central levels. This study aimed to measure how much influence the leadership style of the village head and the competence of village officials had on the success in the development of Sriamur Village in North Tambun, District, Bekasi Regency. The method in this study is a quantitative method, with the number of samples in this study as many as 43 respondents who are village heads, village officials and employees of the North Tambun sub-district. The results showed that the leadership of the village head and village officials in village development was 34.7%. In comparison, the remaining 65.3% was influenced by other factors that could affect the success of development in the village